Analysis of Raw Materials and Production Process of Broiler Feed Crumble Type B-BR 1 MGB: Analisis Bahan Baku dan Proses Produksi Pakan Ternak Ayam Ras Pedaging (Broiler) Jenis Crumble Tipe B-BR 1 MGB - Khabibi, Fikri Maulana (Universitas Muhammadiyah Sidoarjo, 2024)
PT Japfa Comfeed Indonesia, Tbk is a company engaged in animal feed which provides various types, one of which is crumble. Crumble is a granular food processed by the process of grinding and crushing pellets. In addition to pellets, crumble is preferred and more suitable for poultry farms with mechanized feed bins. Crumble-shaped feed products are an activity that combines many existing production factors with the aim of producing a product, which is beneficial to consumers.